Comparative Effects of Neurodynamics With and Without Wrist Splint in patients with Carpal Tunnel Syndrome - Sidrah Shabbir, Farah Naeem, Aqsa Aroob, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare effectiveness of neurodynamics with and without wrist splint in patients with carpal tunnel syndrome.Study design: Randomized controlled trial. Settings: Farooq Hospital & Akhtar Saeed Trust teaching hospital,Lahore. Methodology: In present study 34 patients were randomly allocated into two groups in which each group contains 17 patients. Group A received combined treatment approach of neurodynamics and wrist splint while group B received only neurodynamics for two weeks .Improvement in functions and pain were recorded after 2 weeks .Initially baseline measurements were taken on DASH questioner and VAS. Present RCT study was carried out at Akhtar Saeed Trust Hospital,Lahore. Analysis was established through SPSS. Results: Independent sample t test was applied in present study of 34 patients as the mean difference was greater in group A in which combined treatment approach of wrist splint and neurodynamics were applied as compared to other group B in which only neurodynamics were applied.The p value is < 0.05 which shows results were significant. Results were more significant and superior in group A as compared to group B. Conclusion: Group A in which neurodynamics and wrist splint were used found to be more effective as compared to group B in which only neurodynamics were used. Keywords: Carpal tunnel syndrome; neurodynamics; wrist splint.